Modelling the structural behaviour of a round nozzle to flat plate interface in pressure vessels. (April 2021) - Beyers, Wilhelm André; Venter, Gerhard
Abstract: In the field of pressure vessel design, much research has been done to predict the structural behaviour of round nozzles connected to spherical and cylindrical structures. This has been motivated by the fact that the majority of pressure vessels in industry have round bodies, as these are better suited to withstanding pressure. A large demand however also exists for flat-sided pressure vessels with round nozzles, particularly in the air-cooled heat exchanger industry, but there is a lack of research and guidelines on accurately predicting how these structures behave at the nozzle interface. This paper presents a new model that predicts the linearised stresses occurring in these structures in order to gain a better understanding of how they behave.